2006
DOI: 10.1093/nar/gkl063
|View full text |Cite
|
Sign up to set email alerts
|

Novel GC-rich DNA-binding compound produced by a genetically engineered mutant of the mithramycin producer Streptomyces argillaceus exhibits improved transcriptional repressor activity: implications for cancer therapy

Abstract: The aureolic acid antibiotic mithramycin (MTM) binds selectively to GC-rich DNA sequences and blocks preferentially binding of proteins, like Sp1 transcription factors, to GC-rich elements in gene promoters. Genetic approaches can be applied to alter the MTM biosynthetic pathway in the producing microorganism and obtain new products with improved pharmacological properties. Here, we report on a new analog, MTM SDK, obtained by targeted gene inactivation of the ketoreductase MtmW catalyzing the last step in MTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(150 citation statements)
references
References 55 publications
9
140
0
1
Order By: Relevance
“…This is suggested by the fact that the treatment of Namalwa cells by MTM, which inhibits all transcription factors binding to GC-rich regions (37), abolished the up-regulation of p21 WAF-1 . Sp1, whose binding to DNA is inhibited by MTM (31), is involved in the up-regulation of p21 WAF-1 in several cell types (14,38), as well as in the repression of this gene (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 98%
“…This is suggested by the fact that the treatment of Namalwa cells by MTM, which inhibits all transcription factors binding to GC-rich regions (37), abolished the up-regulation of p21 WAF-1 . Sp1, whose binding to DNA is inhibited by MTM (31), is involved in the up-regulation of p21 WAF-1 in several cell types (14,38), as well as in the repression of this gene (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11][12][13] In order to address these issues, extensive combinatorial biosynthesis has been performed on the MTM pathway and has resulted in several novel analogs. [14][15][16] The present authors have shown that the inactivation of the mtmW gene, which codes for the last enzyme in the MTM biosynthetic pathway, yields the most favorable of the new analogs, MTM SK (SK) and MTMSDK (SDK). 15,16 Both SK and SDK exhibited higher anticancer activity than the native MTM, 15,16 yet their short plasma retention time and low accumulation in tumors remained to be improved.…”
Section: Introductionmentioning
confidence: 92%
“…15 S. argillaceus cells of the M7W1 mutant strain were plated on R5A agar and allowed to grow until spores were formed. After 2 days, colonies began to appear on the plates; after 3 days, spores began to form; and after 4 days, the majority of the cells were present as spores.…”
Section: Biosynthesis Of Sk and Sdkmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial experiments were undertaken to ascertain the effects of mithramycin A, a compound that competitively inhibits binding of Sp1 to target GC boxes (Albertini et al, 2006) on NY-ESO-1 promoter activity in Calu-6 cells. As shown in Figure 1a, mithramycin A (2 Â 10 À6 M) reduced the activity of pGL3/NY762 to 30% of its original activity; in fact, luciferase activity of the promoter-reporter construct in sequential DAC/ DP-treated Calu-6 cells following mithramycin exposure was nearly as low as that observed in vector controltransfected Calu-6 cells, which were exposed to chromatin remodeling agents.…”
Section: Role Of Sp1 In Regulating Ny-eso-1 Expression In Lung Cancermentioning
confidence: 99%